2002
DOI: 10.1515/dmdi.2002.19.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amifostine on Liver Oxidative Stress Caused by Cyclophosphamide Administration to Rats

Abstract: Cyclophosphamide is an inactive cytostatic, which is metabolised into active metabolites mainly in the liver. During bioactivation, reactive oxygen species (ROS) are also formed, which can modify the components of both healthy and neoplastic cells leading to decreased antioxidative capacity. Amifostine is a drug that can inactivate ROS. The aim of the present study was to evaluate the influence of amifostine on the antioxidative system of the liver of rats exposed to cyclophosphamide. Intraperitoneal administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 22 publications
8
46
0
3
Order By: Relevance
“…This observation is in line with many reports that demonstrated apparent elevation in lung TBARS following administration of CP (Patel, 1987;Venkatesan & Chandrakasan, 1995;Stankiewicz et al, 2002). Increased TBARS level observed following CP administration in the current work could be indirectly attributed to the decreased level of GSH; also CP has been proved to induce significant alterations in the activity of NADH and NADPH2, likely to be responsible for the ultrastructural changes within mitochondria which include features of mitochondrial damage with disruption of mitochondrial membranes.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in line with many reports that demonstrated apparent elevation in lung TBARS following administration of CP (Patel, 1987;Venkatesan & Chandrakasan, 1995;Stankiewicz et al, 2002). Increased TBARS level observed following CP administration in the current work could be indirectly attributed to the decreased level of GSH; also CP has been proved to induce significant alterations in the activity of NADH and NADPH2, likely to be responsible for the ultrastructural changes within mitochondria which include features of mitochondrial damage with disruption of mitochondrial membranes.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, adriamycin significantly decreased the GSH levels, but the GSH levels were significantly higher in the amifostine-pretreated group than controls. It has been reported that amifostine increased GSH levels in rats (Issels and Nagele 1989;Dorr et al 1996;Stankiewicz et al 2002). So, amifostine may have favorable effects on adriamycininduced acute cardiotoxicity.…”
Section: Discussionmentioning
confidence: 94%
“…Phosphoramide mustard is believed to have antineoplastic activity, but acrolein, a highly reactive metabolite with a short biological half-life, may be responsible for CP-induced liver damage (Honjo et al, 1988). Recent studies suggest that CP generates reactive oxygen species (ROS), such as the superoxide anion, hydroxyl radical and hydrogen peroxide (H 2 O 2 ), during its oxidative metabolism and suppresses the liver's antioxidant defense mechanisms (Bhattacharya et al, 2003;Stankiewicz et al, 2002).…”
Section: Cyclophosphamidementioning
confidence: 99%